Peri-urban Area Development in the Frame of Industrial De-concentration in Greater Bandung Metropolitan Region - FIRMANSYAH (NIM: 25413047), IMAN
Greater Bandung Metropolitan (GBM) region is identified to have urban decentralization since 1990 in the form of shifting higher population growth from core to periphery. Urban decentralization itself consists of two types; Urban deconcentration and sub-urbanization. Urban de-concentration is manifested, among others, in the form of industrial employment de-concentration. As for sub-urbanization, it has been recently extended to occupy formerly rural areas. Urban functions that widens to rural areas can stimulate peri-urbanization, and among which are industrial employment. In relation with that theoretical frame, this research tries: (a) to investigate whether industrial deconcentration phenomenon occurs in GBM region, by analyzing indicators of core and periphery changing roles in industry, and identifying GBM spatial structure implicated by the pattern of industrial subcenters distribution; (b) to asses peri-urban area development through analysis on indicators of urban characteristics' growth in the periphery and the policy supportings on peri-urbanization process; and (c) to study whether the growing process of industrial concentration in the periphery has things in common with the process of peri-urbanization. Results of this research denote that: GBM's regional industry tents to have been de-concentrated; growth of urban characteristics in the periphery tents to indicate that peri-urbanization is in progress; industrial concentrations' growth process in the periphery compares positively to urban characteristics' development process, and the locations of new industrial subcenters in the periphery fit the locations where urban characteristics develop more intensively. In the mean time, policy supportings on peri-urbanization process show less suitability with industrial distribution pattern in the periphery.